THE LATE PALEOZOIC EVOLUTION OF THE CENTRAL INNER MONGOLIA, CHINA: A PERSPECTIVE FROM METAMORPHIC STUDY - J. R. Zhang; C. J. Wei; H. Chu; Y. P. Chen (Геодинамика и тектонофизика)
The Xing’an-Inner Mongolia Orogenic Belt (XIMOB) exposed in the eastern section of the Central Asian Orogenic Belt (CAOB) is generally thought to have resulted from closure of the Paleo-Asian ocean [Şengör et al., 1993]. However, the current hot debate is focused on whether the orogen formed through continuous subduction and accretion over a prolonged period of time until the closure of the Paleo-Asian ocean at the Early Triassic [Xiao et al., 2003], or through the subduction of the Paleo-Asian ocean and related collision in the Early-Mid Devonian [Xu et al., 2013], and the tectonic setting in the Late Paleozoic to Mesozoic has been a pivotal issue.